Kapitein Winokio is beestig. ([S.l.] : Haiku, 2006)
Bevat 1. Pauw 2. Wasbeer 3. Bever 4. Kameel 5. Schildpad 6. Steenbok 7. Poes 8. Uil 9. Leeuw 10. Havik
ca. 28 min.
Keywords: Dieren; Dierenliedjes; Kinderliedjes